Implementasi Internet Of Things (IOT) Untuk Monitoring Kualitas Tanah Tanaman Herbal Dengan Integrasi QR Code - Gunawan, Indra; Sadali, Muhamad; Ahmadi, Hamzan; Wijaya, Lalu Kerta; Ermawati, Siti (Fakultas Teknik Universitas Hamzanwadi, 2025)
In everyday life, the utilization of herbal plants is still relatively low, due to ignorance of the types and benefits of herbal plants and many plants that wither or die. The factors of plant fertility such as soil moisture and soil temperature. Therefore, this research aims to create an alternative prototype for monitoring the soil quality of herbal plants by utilizing IoT (Internet of Things) technology with the integration of a QR Code as a marker of herbal plant identity at each monitoring location. The research method used is Research and Development (R&D). This research uses ESP32 as a microcontroller to drive electronic devices and soil PH sensors, soil moisture, soil temperature and air temperature and humidity connected to IoT devices. Soil quality data, such as moisture, temperature, and pH levels are collected in realtime and converted into QR codes. This data is then sent to the server for processing and analysis, providing useful information for plant owners to effectively manage soil quality. The results showed that the soil pH, soil moisture, soil temperature and air temperature and humidity measuring instruments can work well and have an accuracy rate of 90% and the data is successfully displayed to the webserver.